Does Surgical Volume and Complexity Affect Cost and Mortality in Otolaryngology–Head and Neck Surgery?. (October 2019) - Redmann, Andrew J.; Yuen, Sonia N.; VonAllmen, Douglas; Rothstein, Adam; Tang, Alice; Breen, Joseph; Collar, Ryan
Objectives: (1) To evaluate whether admission volume and case complexity are associated with mortality rates and (2) evaluate whether admission volume and case complexity are associated with cost per admission. Study Design: Retrospective case series. Setting: Tertiary academic hospital. Subjects and Methods: The Vizient database was queried for inpatient admissions between July 2015 and March 2017 to an otolaryngology–head and neck surgery service. Data collected included admission volume, length of stay, intensive care unit (ICU) status, complication rates, case mix index (CMI), and cost data. Regression analysis was performed to evaluate the relationship between cost, CMI, admission volume, and mortality rate. Results: In total, 338 hospitals provided data for analysis. Mean hospital admission volume was 182 (range, 1-1284), and mean CMI was 1.69 (range, 0.66-6.0). A 1-point increase in hospital average CMI was associated with a 40% increase in odds for high mortality. Admission volume was associated with lower mortality, with 1% lower odds for each additional case. A 1-point increase in CMI produces a 4624 higher total cost per case (95% confidence interval, 4550-4700), and for each additional case, total cost per case increased by 6. Conclusion: For otolaryngology inpatient services at US academic medical centers, increasing admission volume is associated with decreased mortality rates, even after controlling for CMI and complication rates. Increasing CMI levels have an anticipated correlation with higher total costs per case, but admission volume is unexpectedly associated with a significant increase in average cost per case.